2013
DOI: 10.1016/j.addbeh.2013.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Motivations to quit cannabis use in an adult non-treatment sample: Are they related to relapse?

Abstract: Background The majority of cannabis smokers who quit do so without formal treatment, suggesting that motivations to quit are an important part of cessation process. However, little is known about how motivations relate to successful quitting. Method A convenience sample of 385 non-treatment-seeking adult cannabis smokers (58% male, age 16–64 years at start of quit attempt) who made a “serious” (self-defined) quit attempt without formal treatment while not in a controlled environment were administered the 176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 31 publications
(51 reference statements)
1
22
0
Order By: Relevance
“…It is difficult to determine if our results are consistent with retrospectively reported reasons for quitting because these studies asked mostly about internal states, not environmental cues. However, social influences and health problems (both of which were found predictive in the current study) were often cited as reasons for quitting in prior retrospective studies (Ellingstad et al, 2006; Copersino et al, 2006; Chauchard et al, 2013); thus, our study can be seen as a more experimentally rigorous validation that these are important reasons for quitting or reducing.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…It is difficult to determine if our results are consistent with retrospectively reported reasons for quitting because these studies asked mostly about internal states, not environmental cues. However, social influences and health problems (both of which were found predictive in the current study) were often cited as reasons for quitting in prior retrospective studies (Ellingstad et al, 2006; Copersino et al, 2006; Chauchard et al, 2013); thus, our study can be seen as a more experimentally rigorous validation that these are important reasons for quitting or reducing.…”
Section: Discussionmentioning
confidence: 49%
“…The few studies that examined predictors of attempts to stop or reduce cannabis have reported retrospective reasons for quitting that mostly tap cognitive states (e.g., desire to prove self-control; Ellingstad et al, 2006; Copersino et al, 2006; Chauchard et al, 2013). Several empirical studies have shown recall of such subjective states is often inaccurate due to memory and rationalization biases, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some work has shown cross-substance links with respect to motivation, additional work is needed to better understand the impact of motives not only on cognitively-based factors important to quit processes, but also the impact on actual success in quitting. Recent work in this arena has shown that among non-treatment seeking cannabis smokers have motives similar to cigarette smokers who later quit without formal treatment 12 . While this work evinced relations among motives and quit success in a convenience sample 12 , there still exists a gap in knowledge with respect to quit success among treatment-seeking samples, and as such, further examination is needed.…”
mentioning
confidence: 99%
“…Recent work in this arena has shown that among non-treatment seeking cannabis smokers have motives similar to cigarette smokers who later quit without formal treatment 12 . While this work evinced relations among motives and quit success in a convenience sample 12 , there still exists a gap in knowledge with respect to quit success among treatment-seeking samples, and as such, further examination is needed.…”
mentioning
confidence: 99%